2019
DOI: 10.3389/fmicb.2019.02052
|View full text |Cite
|
Sign up to set email alerts
|

Genomics of Urea Transport and Catabolism in Cyanobacteria: Biotechnological Implications

Abstract: Cyanobacteria are widely-diverse prokaryotes that colonize our planet. They use solar energy to assimilate huge amounts of atmospheric CO2 and produce a large part of the biomass and oxygen that sustain most life forms. Cyanobacteria are therefore increasingly studied for basic research objectives, as well as for the photosynthetic production of chemicals with industrial interests. One potential approach to reduce the cost of future bioproduction processes is to couple them with wastewater treatment, often pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 62 publications
7
68
0
Order By: Relevance
“…The results showed that cells grew well on urea up to 2 mM, whereas higher urea concentrations reduced the duration of healthy growth and production of biomass ( Supplementary Figure S1). After 7-10 days of cultivation on urea, Cyanothece PCC 7425 can turn yellowish, as previously observed in the phylogenetically distant cyanobacteria Anabaena cylindrica, Synechococcus PCC 7002 (Sakamoto et al, 1998) and Synechocystis PCC 6803 growing on urea as the sole nitrogen source (Veaudor et al, 2019). Again as observed in Synechocystis PCC 6803 (Veaudor et al, 2018), once installed the chlorosis process decreased the cell viability measured by plating assays on standard growth medium (it contains nitrate, not urea).…”
Section: Identification Of Effective Conditions For the Growth Of Cyasupporting
confidence: 67%
See 3 more Smart Citations
“…The results showed that cells grew well on urea up to 2 mM, whereas higher urea concentrations reduced the duration of healthy growth and production of biomass ( Supplementary Figure S1). After 7-10 days of cultivation on urea, Cyanothece PCC 7425 can turn yellowish, as previously observed in the phylogenetically distant cyanobacteria Anabaena cylindrica, Synechococcus PCC 7002 (Sakamoto et al, 1998) and Synechocystis PCC 6803 growing on urea as the sole nitrogen source (Veaudor et al, 2019). Again as observed in Synechocystis PCC 6803 (Veaudor et al, 2018), once installed the chlorosis process decreased the cell viability measured by plating assays on standard growth medium (it contains nitrate, not urea).…”
Section: Identification Of Effective Conditions For the Growth Of Cyasupporting
confidence: 67%
“…Cyanobacteria, the oldest and largest phylum of prokaryotes that perform the plant-like photosynthesis (Schirrmeister et al, 2015), are regarded as the ancestors of the plant chloroplast (Ponce-Toledo et al, 2017) and the purveyors of the oxygen that shaped our biosphere (Hamilton et al, 2016). Contemporary cyanobacteria still capture a vast quantity of solar energy to assimilate huge amounts of CO 2 (Dai et al, 2018) and nitrogen (nitrate, ammonium or urea) (Singh et al, 2016;Veaudor et al, 2019) to produce an enormous biomass that sustain most life forms on our planet. In colonizing most waters (fresh, brackish and marine) and soils (even deserts) biotopes, cyanobacteria have developed as widely diverse organisms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Synechocystis can also utilize urea, which is imported into the cell via a transporter complex composed of five subunits, UrtA-E [208]. Urea is converted into two molecules of ammonia via the urease complex comprising three subunits, UreA-C, which is assembled by four accessory proteins, UreD-G [209].…”
Section: Ammonia Nitrate Nitrite and Urea Transportmentioning
confidence: 99%